Nutritional management of high output enterocutaneous fistula: Case report. - Sari, Eka Maya (IJCNP : INDONESIAN JOURNAL OF CLINICAL NUTRITION PHYSICIAN, 2026)
Enterocutaneous fistula is a common post-operative gastrointestinal surgery complication with high morbidity and mortality rate. High morbidity and mortality rate in enterocutaneous fistula is due to malnutrition, dehydration and electrolyte disturbances. Comprehensive management needed to support optimal therapy of enterocutaneous fistula including nutritional therapy. We present of a case of an enterocutaneous fistula after gastrointestinal surgery which cause malnutrition. This case demonstrates that adequate nutritional management of enterocutaneous fistula plays important role in healing process.